High-speed multi-channel long-haul coherent optical transmission system - Muthanna Ali Kadhim; Ali Yousif Fattah; Atheer Alaa Sabri (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
In this work, high-speed transmission over the long-haul optical channel using orthogonal frequency division multiplexing (OFDM) was investigated. Furthermore, we recommend mixing polarization division multiplexing (PDM) with coherent OFDM (CO-OFDM) and quadrature amplitude modulation (16-QAM) to improve spectral efficiency (SE) while transmitting over a wavelength division multiplexing (WDM) system. An 800 Gb/s WDM PDM-CO-OFDM-16QAM transmission system with various channel spacing of 100 GHz, 50 GHz, and 25 GHz is examined utilizing the OptiSystem (2021) version 18.0 software package over ten spans of 60 km standard single-mode fiber (SSMF). Different channel spacing WDM systems have been compared in terms of performance and SE. The results reveal that the WDM system with 100 GHz channel spacing has a longer transmission range and needs minimal optical signal to noise ratio (OSNR) at the reception. The 25 GHz channel spacing WDM system exceeds the others in terms of SE. Further, the effect of ultra-low loss and large effective area fiber in lowering span loss and nonlinear effects for 25 GHz channel spacing WDM system is investigated. The findings show that the system performance with the new fiber outperforms the SSMF. The acceptable bit error rate (BER) for this study is 0.033 (20% concatenated forward error correction (FEC) threshold).